Enhanced the simultaneous removal and recovery of phosphorus in induced crystallization coupled biological phosphorus removal process - Gongfeng Xin; Xiaoteng Zhou; Peng Zuo; Weiwei Ma; Cong Liu; Yi Zhao (Green Technologies and Sustainability, 2024)
Remove and recovery of phosphorus from wastewater is expected to be a promising strategy to solve the shortage of phosphorus resources and control the water environment pollution. In this study, induced crystallization coupled biological phosphorus removal (IC-BPR) process was established to achieve simultaneous removal and recovery of phosphorus in wastewater. The effects of side stream ratio (SSR) on the removal and recovery efficiency of phosphorus and the microbial community structure were explored. The results indicated that the SSR of 40% was optimal to phosphorus removal and recovery in the IC-BPR. The total phosphorus removal efficiency was 94.23% under the SSR of 40%, of which the phosphorus removal efficiency by IC accounted for 74.87%. And the total phosphorus recovery efficiency was 67.29%. The particle size and crystal structure analysis of the crystallized products indicated that the increase of SSR was conductive to heterogeneous crystallization. Furthermore, typical polyphosphate accumulation organisms (PAOs), including Rhodocyclaceae, Acinetobacter, and Dechloromonasin, were enriched under the side stream ratio of 40%. And functional genes related to amino acid transport and metabolism, energy production and conversion were activated. The above results indicated that the IC could significantly enhance the removal and recovery of phosphorus under a suitable SSR condition. It will provide important reference for wastewater treatment coupled phosphorus resource recovery technology.